A novel 3D sandwich structure of hybrid graphite nanosheets and silver nanowires as fillers for improved thermal conductivity. (30th January 2017) - Zhuang, Xiao; Zhou, Yongcun; Liu, Feng
Abstract: We explored a novel 3D sandwich structure of fillers in the polymer matrix to enhance thermal conductivity. A variety of fillers in the polymer matrix play a significant role in the physical properties of the composite. Fillers containing particle and line structures are popular, and enhance the thermal and electrical conductivities. Therefore, filler-based matrix network improves conductivity. We propose a sandwich structure consisting of hybrid graphite nanosheets (two dimensions), and silver nanowires (AgNWs) (one dimension), to create a 3D sandwich structure of polyimide matrix with improved thermal conductivity. Surface treatment of graphite and silver nanowires were conducted to reduce the dielectric constant of the composite. We designed the filler of 20 wt% resulting in a high thermal conductivity of 3.21 W m −1 K −1 with 15% C@SiO2 and 5% AgNWs@SiO2 filler loading. The novel combination and structure markedly enhanced the thermal conductivity of the composite.